The last kingdom. Season three [videorecording (DVD)]. - Dreymon, Alexander, 1983-; Dawson, David, 1982-; Cox, Emily, 1985-; Macfadyen, Matthew, 1974- (Universal, 2018)
Dark forces are moving outside the court and when a powerful Danish warlord Bloodhair attacks, Uhtred must lead Wessex's forces into battle. He captures Bloodhair's mysterious lover, the savage sorceress Skade, who throws a curse and his world becomes blighted by tragedy.